The Influence of Ticket Prices and Physical Facilities on Visitor Interest at the Sunrise Point Sunan Ibu Tourist Attraction in Ciwidey, Bandung Regency, Indonesia - Supriyatna, Wawan (Manunggal Halim Jaya, 2025)
This study examines the influence of ticket prices and facilities on visitor interest at the Sunrise Point Sunan Ibu tourist attraction in Ciwidey, Bandung Regency. Employing a quantitative approach with a survey method, the research involved a population comprising all visitors to the site during the study period, with a sample of 81 respondents selected through purposive sampling. Data were gathered using a closed-ended questionnaire and analyzed using multiple linear regression. The results revealed that both ticket prices and facilities positively and significantly impact visitor interest, individually and collectively. These findings suggest that appropriate pricing and the availability of adequate facilities can effectively enhance tourist interest. Consequently, the study provides valuable insights for tourism managers in formulating development strategies that prioritize visitor satisfaction and comfort, thereby supporting sustainable tourism.